Frontier Encounters 2012
DOI: 10.11647/obp.0026.07
|View full text |Cite
|
Sign up to set email alerts
|

Prostitution and the Transformation of the Chinese Trading Town of Ereen

Abstract: He is the coordinator of an ESRC-funded project (2012-2015) entitled 'Where Rising Powers Meet: Russia and China at their northeast Asian border'. He previously carried out research in Mongolia where he investigated the prevalence of anti-Chinese sentiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…At this time, pawnshops arose in urban centresan occupational category that buys goods and sells money (Højer 2012). And 'changers' (chengüüd, from the English '[ex]change') also arose in Magtaalbulkers who buy resources from many sources, bulk it, move it, and resell it at higher prices (Højer 2012;Lacaze 2010Lacaze , 2012. In her book on the international trade around matsutake mushrooms, Tsing (2015, 62-66) discusses how supply chain capitalism takes advantage of non-capitalist processes (what she calls 'salvage accumulation') and converts or 'translates' it into economic value.…”
Section: Moneylenders As Translators Across Registersmentioning
confidence: 99%
“…At this time, pawnshops arose in urban centresan occupational category that buys goods and sells money (Højer 2012). And 'changers' (chengüüd, from the English '[ex]change') also arose in Magtaalbulkers who buy resources from many sources, bulk it, move it, and resell it at higher prices (Højer 2012;Lacaze 2010Lacaze , 2012. In her book on the international trade around matsutake mushrooms, Tsing (2015, 62-66) discusses how supply chain capitalism takes advantage of non-capitalist processes (what she calls 'salvage accumulation') and converts or 'translates' it into economic value.…”
Section: Moneylenders As Translators Across Registersmentioning
confidence: 99%
“…By contrast, my research has not found shame to be the only or even the primary emotion expressed by Russians facing China. Gender hierarchies are structured differently in Eastern Europe, and sexuality is less associated with guilt/shame (Lacaze 2012). Furthermore, any affect Russian border crossers feel at purchasing and absorbing the materiality of the newly rampant 'other' is complicated.…”
mentioning
confidence: 99%